Liquisolid ibuprofen tablets - Lannie Hadisoewignyo; Evania hadi; Nehru Wibowo (Indonesian Journal of Pharmacy, 2011)
Ibuprofen  is  an  antiinflamatory  drugs  with  poor  solubility  in  water  but good  permeability  in  the  gastrointestinal  tract.  Liquisolid  tablet  is  the  one method of increasing solubility and dissolution rate of ibuprofen. The aims of this study  was  to  determine  the  effect  of  glycerine  and  propylene  glicol  as  non volatile  solvent  and  PVP  K-30   as  hydrophilic  polymer  on the  dissolution  rate of liquisolid  ibuprofen  tablets.  In  this  research,  there  are  7  formulas  of  liquisolid ibuprofen  tablets  were  made.  The  ratio of  ibuprofenin  glycerine  is 1  : 3  and of propilene glicol is 5:1 with various concentration of PVP K-30 (5, 10, and 15%). Formula I was made as a control so there was no addition of non volatile solvent and hydrophilic polymer. Based on the results, liquisolid ibuprofen tablets using glycerine  or  propylene  glycol  as  a  non  volatile  solvent  and  PVP  K-30  as  a hydrophilic  polymer  can  increase  the  dissolution  rate  constant  of  liquisolidibuprofen  tablets  comparedthat  of  ibuprofen  conventional  tablets  (non liquisolid).  The  addition  of  PVP  K-30  as  a  hydrophilic  polymer  can  increase  the dissolution  rate  constants  liquisolid  ibuprofen  tablets  until  a   concentration  of more  than  10%  because  the  polymer  will  swell  and  form  a  viscous  layer  that inhibits the disintegration so that the percent release decrease.Key words:Ibuprofen, liquisolid, non volatile solvent, hydrophilic polymer.